(untitled) (Research, Society and Development, 2024)
This research aims to compare climatic conditions in different areas of the municipality of Assú/RN, located in the Brazilian Caatinga. A low-cost climate monitoring system was developed to detect significant differences in the climate of degraded and preserved areas. To achieve the objective, the research followed the following steps: 1) Delimitation of the study area (three experimental units were demarcated: Floresta Nacional de Açu - FLONA, Urban Area - AU, and Degraded Rural Area - ARD); 2) Development and implementation of the prototype with hardware and software; 3) Data analysis and discussion, using the Shapiro-Wilk and Levene tests to check for normality and homogeneity. Analysis of variance (ANOVA) detected significant differences between the areas, with p < 0.05, followed by the Tukey test to determine which experimental units differed significantly from each other. All statistical analyses presented in the research were conducted using R Software. FLONA showed the most favorable climatic indices, with lower temperatures, higher relative humidity, lower CO2 concentration, and UV radiation values consistent with the season. The area also plays a crucial role in combating the desertification of the Caatinga, and its expansion, advocated by ICMBio, is of utmost importance in promoting the sustainable use of natural resources, encouraging environmental education, and fostering scientific research.